2021
DOI: 10.3390/molecules26010205
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin: A Glycoprotein Involved in Immunomodulation, Anticancer, and Antimicrobial Processes

Abstract: Lactoferrin is an iron binding glycoprotein with multiple roles in the body. Its participation in apoptotic processes in cancer cells, its ability to modulate various reactions of the immune system, and its activity against a broad spectrum of pathogenic microorganisms, including respiratory viruses, have made it a protein of broad interest in pharmaceutical and food research and industry. In this review, we have focused on describing the most important functions of lactoferrin and the possible mechanisms of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 143 publications
(82 reference statements)
0
31
0
3
Order By: Relevance
“…aeuruginosa, H. pylori, Enterobacter, Yersinia, Porphyromonas gingivalis and Klebsiella pneumoniae. Besides, this protein had antibacterial activities against Gram-positive bacteria such as Listeria monocytogenes, Bacillus and S. aureus [65]. Likewise, lactoferrin has been used against different yeasts such as C. dubliniensis, C. albicans, C. glabrata, and Cryptococcus, in synergy with different antifungal drugs [66].…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%
“…aeuruginosa, H. pylori, Enterobacter, Yersinia, Porphyromonas gingivalis and Klebsiella pneumoniae. Besides, this protein had antibacterial activities against Gram-positive bacteria such as Listeria monocytogenes, Bacillus and S. aureus [65]. Likewise, lactoferrin has been used against different yeasts such as C. dubliniensis, C. albicans, C. glabrata, and Cryptococcus, in synergy with different antifungal drugs [66].…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%
“…Considering the high concentration of LF in human milk, it can be concluded that it is extremely important for the proper development and protection of the newborn. It can significantly reduce the risk of infection because of pathogens when the baby’s body is not yet sufficiently protected by its immune system [ 188 ].…”
Section: Maternal Lactoferrin (Lf) In Covid-19—pregnancymentioning
confidence: 99%
“…Esta proteína parece presentar actividad antitrombótica y capacidad para inhibir la replicación de virus. De hecho, parece que esta proteína podría jugar un papel importante en la defensa contra la infección por SARS-CoV-2 debido a que es capaz de unirse a una proteína específica de membrana, bloqueando la interacción preliminar del virus con las células huésped (7).…”
Section: Proteínas Y Péptidos Bioactivosunclassified
“…Sin embargo, al ser la leche un alimento consumido diariamente, contribuye de manera importante a la ingesta total de estos nutrientes en la dieta de la población. Por último, cabe señalar que es la tercera fuente dietética de vitamina B 12 y vitamina D, y la segunda fuente de magnesio (7).…”
Section: Papel De La Leche Y Sus Componentes Naturalesunclassified